APPLICATION OF THE MODEL PROBLEM BASED LEARNING TO IMPROVE LEARNING OUTCOMES IN MATHEMATICS SUBJECT ADDING AND SUBTRACTING WHOLE NUMBERS - Hendayani, Yesi; Sukmanasa, Elly; Nurlaela, Epon (Journal of Educational Review and Research, 2023)
This research is a collaborative classroom action research designed with the aim of knowing the learning outcomes of class IV students at SDN Julang, Bogor City regarding the application of the model.problem based learning in mathematics subjects, the material is addition and subtraction of whole numbers up to 1,000. This type of research is collaborative classroom action research which consists of 2 cycles. The subjects of this research were class IVA students. The results of this research show an improvement in the learning process, changes in student behavior and learning outcomes. Cycle I learning process with a percentage of 96 % then cycle II increased with a percentage of 97%, changes in attitudes of students in cycle I with a percentage of 88%, then cycle II with a percentage of 94% and the learning completion results of cycle I students were 48% which were completed, then cycle II increased by 92% which were completed . All aspects studied increased from cycle I to cycle II. Thus, it can be concluded that the application of the P modelroblem Based Learning can improve the learning outcomes of class IVA students at SDN Julang, Bogor City.